TRADITIONAL CULTURE AS A SUBJECT OF PHILOSOPHICAL REFLECTION - Даренская, В. Н. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The author considers the ethos of working, which is formed in Eastern-Slavonic traditional folk’s culture.